2012
DOI: 10.1371/journal.pone.0036340
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of the E3 Ubiquitin Ligase C-Terminus of Heat Shock Cognate 70 Interacting Protein (CHIP) Produces Specific Behavioral Impairments

Abstract: The multifunctional E3 ubiquitin ligase CHIP is an essential interacting partner of HSP70, which together promote the proteasomal degradation of client proteins. Acute CHIP overexpression provides neuroprotection against neurotoxic mitochondrial stress, glucocorticoids, and accumulation of toxic amyloid fragments, as well as genetic mutations in other E3 ligases, which have been shown to result in familial Parkinson's disease. These studies have created a great deal of interest in understanding CHIP activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 51 publications
3
19
0
Order By: Relevance
“…The role of mitophagy has come under particular scrutiny lately as an increasing number of proteins have linked neurodegeneration with aberrant mitophagy (4, 5, 52, 59). Acute overexpression of CHIP is neuroprotective against a number of acute and chronic stressors, and we recently reported that CHIP KO mice are uniquely impaired by the loss of this ligase, which dramatically decreases life span (8), impairs motor skills (29,38), and alters anxiety responses (29). We show in the current work that these mice also present with atypical CNS protein oxidation and lipid peroxidation, decreased antioxidant responses, and impaired bioenergetic status at baseline.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The role of mitophagy has come under particular scrutiny lately as an increasing number of proteins have linked neurodegeneration with aberrant mitophagy (4, 5, 52, 59). Acute overexpression of CHIP is neuroprotective against a number of acute and chronic stressors, and we recently reported that CHIP KO mice are uniquely impaired by the loss of this ligase, which dramatically decreases life span (8), impairs motor skills (29,38), and alters anxiety responses (29). We show in the current work that these mice also present with atypical CNS protein oxidation and lipid peroxidation, decreased antioxidant responses, and impaired bioenergetic status at baseline.…”
Section: Discussionsupporting
confidence: 57%
“…We recently reported that C-terminus of HSC70-interacting protein (CHIP) haploinsufficiency results in mild behavioral impairments and profound changes in motor function in young animals (29). These data are particularly striking given that deletion of Parkin has a benign phenotype (43), whereas loss of CHIP is catastrophic early in life, resulting in the death of *30% of animals by postnatal day (PND)40 (8,38).…”
mentioning
confidence: 99%
“…Sessions were recorded by a ceiling‐mounted video camera connected to a computer using video acquisition and analysis software (ANY‐maze, Stoelting, Wood Dale, IL). Data analyzed included the amount of time in andnumber of entries into each zone of the maze (Carpenter et al, 2012; McLaughlin et al,2012).…”
Section: Methodsmentioning
confidence: 99%
“…Locomotor activity in a novel open field was measured using commercial open field activity chambers (Med Associates, 27 cm × 27 cm × 20.5 cm) that were contained within light‐ and air‐controlled environmental chambers (Med Associates, 64 cm × 45 cm × 42 cm). Location and movement were detected by the interruption of infrared beams by the body of the mouse (16 photocells in each horizontal direction as well as 16 photocells elevated 4 cm to measure rearing) and were measured by the Med Associates Activity Monitor program (McLaughlin et al,2012; Stanwood and Levitt,2007b). Activity was measured for a 60‐min session.…”
Section: Methodsmentioning
confidence: 99%
“…Behavioral despair was assessed in the forced swim test using plastic cylinders (14.5 cm in diameter, 21 cm in height) filled approximately ¾ full with room temperature water [34,36].…”
Section: Forced Swim Testmentioning
confidence: 99%